Dynamic modeling for a 6-DOF robot manipulator based on a centrosymmetric static friction model and whale genetic optimization algorithm. (September 2019) - Zhang, Libin; Wang, Jiacai; Chen, Jiaoliao; Chen, Kang; Lin, Bangyang; Xu, Fang
Highlights: CSFM is developed to describe hysteresis effect of joint friction. A novel WOA-GA is proposed to identify the robot model of a manipulator. CSFM can improve the estimated torque precision for slow motion by 19–38%. The robot dynamics with CSFM and WOA-GA can give a high accuracy with 93.86%. Abstract: The robot dynamics model can improve the efficiency of robot manipulators to perform complex tasks. In this study, a novel method is proposed for the dynamics model of a 6 degree of freedom (DOF) robot manipulator to improve the motion accuracy. A centrosymmetric static friction model (CSFM) integrated with a piecewise function is utilized to describe the hysteresis effect of joint friction. A hybrid whale optimization algorithm and genetic algorithm (WOA-GA) is applied to identify dynamic parameters of the 6 robot joints. An experiment conducted on a 6-DOF robot manipulator demonstrates that the mean deviation of the estimated torque of robot joints for slow motion is reduced by 19% using CSFM in contrast to the Stribeck model. The mean match degree of the estimated torque can reach to 93.86% based on WOA-GA, improved by 0.4–2% compared with other optimization algorithms (WOA, GA and PSO-GA). These results prove that the method based on CSFM and WOA-GA is feasible for the precise dynamics model of a robot manipulator.